The Analysis Study of Histopathologic Diagnosis of Primary Malignant Melanoma of Esophagus : An Anatomic Pathology Comprehensive Systematic Review - Prastyo, Wahyu Agus; Nugraheni, Artha Investari; Ayuningrum, Mutia Ruliana (International Medical Journal Corp. Ltd, 2024)
Background: Esophageal melanoma is believed to develop from melanocytes anchored in the esophageal mucosa. The aim of this study to show about histopathologic diagnosis of primary malignant melanoma of esophagus. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: A primary malignant melanoma of the esophagus (PMME) is a highly malignant tumor with a poor prognosis. A primary malignant melanoma of the esophagus (PMME) diagnosis should be made by combining clinical imaging and relying on histopathological and immunohistochemical markers. Diagnosis in the early stages and differential diagnosis, timely operation therapy, and postoperative appropriate chemotherapy and immune therapy combined with the initial patient condition may prolong survival time.